Microbial Physiology Governs the Oceanic Distribution of Dissolved Organic Carbon in a Scenario of Equal Degradability - Mentges, Andrea; Deutsch, Curtis; Feenders, Christoph; Lennartz, Sinikka T.; Blasius, Bernd; Dittmar, Thorsten (Frontiers in Marine Science, 2020)
Dissolved organic carbon (DOC) forms one of the largest active organic carbon reservoirs on Earth and reaches average radiocarbon ages of several thousand years. Many previous large scale DOC models assume different lability classes (labile to refractory) with prescribed, globally constant decay rates. In contrast, we assume that all DOC compounds are equally degradable by a heterotrophic microbial community. Based on this central assumption, we simulate DOC concentrations using a simple biogeochemical box model. Parameterized correctly, the simple model of neutral DOC uptake produced a recalcitrant carbon pool of 33mmolC/m3, throughout the entire virtual ocean. The spatial distribution of DOC in the model was independent of the distribution of DOC sources from primary production and particle degradation. Instead, DOC concentrations were primarily driven by spatial gradients in microbial physiology, e.g. mortality rate or growth efficiency. Applying such a gradient, we find DOC concentrations of ~70mmolC/m3 at the surface and ~35mmolC/m3 in the deep ocean. Introducing model variations such as seasonally-varying supply rates or temperature-dependent DOC uptake did not significantly alter model results. DOC spatial patterns are thus not necessarily shaped by the co-cycling of separate reactivity fractions, but can also arise from gradients in physiological parameters determining DOC uptake. We conclude that neutral DOC uptake can lead to realistic large-scale patterns of DOC concentration in the ocean.